Natalizumab and fumarate treatment differentially modulate CD4+ T cell and B cell subtypes in multiple sclerosis patients without impacting durable COVID-19 vaccine responses - Curtin, Ryan; Velmurugu, Yogambigai; Dibba, Fatoumatta; Hao, Yuan; Nyovanie, Samantha; Lopez, Andrea; Mieles, David; Ng, Courtney; Perdomo, Katherine; Scott, Nicole; Lewin, James B.; Avila, Robin L.; et al. (Frontiers in Immunology, 2025)
BackgroundThere is a greater risk of complications from severe COVID-19 in immunocompromised patients with multiple sclerosis (pwMS) treated with certain disease-modifying therapies (DMTs), as well as a diminished vaccine response.MethodsIn this exploratory, observational study, we recruited 28 patients with Relapsing Remitting MS (RRMS, n=24) or Secondary Progressive MS (SPMS, n=4), that were receiving treatment with either natalizumab or fumarates (diroximel or dimethyl) prior to baseline sample collection. Blood samples were collected before vaccination (baseline), between 4 weeks and 6 months post vaccination, and post booster administration. A multiplex bead immunoassay (MBI) was used to measure anti-Spike IgG, while IFNγ and IL-2 ELISpot assays were used to determine T cell activation. A 35-color spectral flow cytometry panel was used to phenotype bulk B and T cells and SARS-CoV-2-specific T cells, while dimensionality reduction was performed for further phenotypic analysis.ResultsWe observed a significantly increased absolute lymphocyte count (ALC) (p=0.0003) in natalizumab-treated pwMS when compared to fumarate-treated pwMS primarily due to increased circulating CD19+ B cells. Fumarate-treated pwMS exhibited a diminished Th1/Th2 ratio when compared to natalizumab-treated pwMS (p=0.0004) or healthy controls (p=0.0745), while natalizumab treatment marginally increased the Th1/Th2 ratio compared to healthy controls (p=0.1311). The observed increase in B cells in natalizumab-treated pwMS were predominantly memory B cells, and double negative (DN) B cells. However, no significant differences between the treatment groups were seen in terms of Spike IgG titers following the initial vaccination course or booster dose, nor in SARS-CoV-2-specific CD4+ responses, all of which remained robust for at least 6 months post-vaccination. The magnitude of humoral and cellular immune responses in both treatment groups were comparable to vaccinated healthy controls. Additionally, SARS-CoV-2 spike-specific CD4+ T cell phenotyping revealed a Th2 dominant response to booster dose in natalizumab-treated pwMS (p=0.0485) but not fumarate-treated pwMS.ConclusionpwMS treated with natalizumab or fumarates exhibit similarly robust and durable SARS-CoV-2 specific T cell and humoral responses following vaccination and booster dose. DMT-treated pwMS showing comparable responses to healthy individuals following initial vaccination supports the notion that treatment with these specific DMTs does not diminish strong, long-lasting immunity conferred by COVID-19 vaccination, despite the phenotypic differences modulated by each therapy.